Dairy Processing Technology - G. K. Najmitdinova (European Science Publishing, 2023)
This article provides scientific information about the technology of processing dairy products, as well as the biologically active components of dairy products, their nutritional value, and the correct use of pasteurized and sterilized milk in the food industry.
Keywords: Milk, chemical composition, protein, fat, solids, pasteurized milk, sterilized milk.